A formulation containing Cymbopogon flexuosus essential oil: improvement of biochemical parameters and oxidative stress in diabetic rats - Ailton Santos Sena-Júnior; Cleverton Nascimento Santana Andrade; Pedro Henrique Macedo Moura; Jocsã Hémany Cândido dos Santos; Cauãn Torres Trancoso; Eloia Emanuelly Dias Silva; Deise Maria Rego Rodrigues Silva; Ênio Pereira Telles; Luiz André Santos Silva; Isabella Lima Dantas Teles; Sara Fernanda Mota de Almeida; Daniel Alves de Souza; et al. (Beilstein Journal of Nanotechnology)
Diabetes mellitus (DM) is a highly prevalent public health problem characterized by hyperglycemia that causes complications due to the generation of reactive oxygen species and oxidative damage. Studies have shown that essential oils containing citral, such as lemongrass, have various biological activities, including bactericidal, antiviral, antifungal, antioxidant, and hypoglycemic effects. Therefore, this study aims to obtain a microemulsified formulation containing the essential oil of Cymbopogon flexuosus (EOCF) and to evaluate its antioxidant and antidiabetic activity in diabetic rats. The microemulsion (ME) was obtained after consulting the corresponding pseudoternary phase diagram and showed stability, isotropy, Newtonian behavior, nanometric size (15.2 nm), and pH 4.2. Both EOCF and the ME showed high antioxidant activity, but the ME resulted in greater antioxidant activity, potentiating the activity of isolated EOCF. Finally, male Wistar rats (3 months old, 200–250 g) with streptozotocin-induced type-1 DM were supplemented with EOCF and ME (32 mg/kg) for 21 days. Both EOCF and ME supplementation resulted in reduced blood glucose levels and improved lipid profiles when compared to the control group. Additionally, the ME was able to provide additional benefits, such as reduced liver damage, improved renal function, reduced systemic inflammation, and increased high-density lipoprotein levels. Overall, the results show that EOCF was efficiently incorporated into the microemulsion, improving its antioxidant activity and showing promising results for use in the treatment of DM via the oral route.